A cross-sectional study of post-vaccination anti-HBs titer and knowledge of hepatitis B infection amongst medical students in a metropolitan city - Acchammachary, Ashmaki A.; Ubale, Milind; Belurkar, Deepali D.; Bhave, Poorva P.; Malgaonkar, Aniruddha Arjun; Kartikeyan, Sundaram (International Journal of Research in Medical Sciences, 2016)
Background: Medical students are at risk of acquiring hepatitis B virus infection due to occupational contact with patients’ blood or other body fluids. This study was conducted to determine knowledge of hepatitis B virus infection and anti-HBS antibody titer amongst medical students. Methods: This cross-sectional observational study was conducted on medical students who satisfied the intake criteria and gave written informed consent to participate in the study. After Institutional Ethics Committee clearance, written informed consent was obtained and a structured, pre-validated questionnaire (pre-test) was administered to the participants. After an educational session, an identical questionnaire was administered (post-test). For determining anti-HBs titer (vaccinated participants) and HBsAg (non-vaccinated participants), blood was aseptically collected by cubital venepuncture. HBsAg and anti-HBs antibody levels were determined by immuno-chromatographic assay and enzyme-linked immunosorbent assay, respectively. Results: 140 healthy, HBsAg-negative medical students (79 males; 61 females) participated in the present study. There was increased median correct response in the post-test with increased minimum and first quartile. 91 (65%) who were vaccinated against Hepatitis B were enrolled for anti-HBs titer estimation. There was no significant gender difference in mean antibody titer. 19 (20.9%) had inadequate levels of anti-HBS antibodies. 50% seroconversion was seen after single dose of hepatitis B vaccine. Conclusions: It is essential to delve into the logistic aspects of evaluating all medical students for hepatitis B infection, procuring and offering free vaccination and assessing anti-HBS titer of vaccinated individuals.